Good Quality Discussion is Necessary but Not Sufficient in Asynchronous Tuition: A Brief Narrative Review of the Literature - William James Fear; Andrew Erikson-Brown (Online Learning, 2014)
Online learning is a growing field of education with a corresponding increase in the use of asynchronous discussion. Asynchronous discussion is a form of interaction that is mediated rather than direct and where there is a time lag in the interactions between discussants. In this paper we conducted a brief narrative review of the literature on asynchronous discussion. We argue, initially, that discussion is necessary, but not sufficient, for successful pedagogic outcomes and more so in the case of online learning. We identified agreement in the literature on what can be considered the key factors for successful asynchronous discussion.